"Present Through It All": A Qualitative Exploration of Psychotherapy and Psychosis. (November 2019) - Adame, Alexandra L.
This article provides an overview of a qualitative study that focused on psychotherapists' experiences of working with people struggling with psychosis. I interviewed four therapists in private practice about their experiences working with this population and describe many aspects of their work including how they understood the nature of psychosis, how they envision process of psychotherapy, and challenges they have faced. I used interpretive phenomenological analysis to analyze the therapists' interviews. The findings of this project highlight the necessity of a supportive therapy relationship and the therapists' genuine interest and respect for their clients.